2009
DOI: 10.1038/modpathol.2009.108
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated rhabdomyomatous tumors after chemotherapy for metastatic testicular germ-cell tumors: a clinicopathological study of seven cases mandating separation from rhabdomyosarcoma

Abstract: To gain insight concerning prognosis, we investigated seven cases of post-chemotherapy retroperitoneal lymph-node dissections from patients with testicular germ-cell tumors that contained sizable nodules of differentiated skeletal muscle, but that lacked both a primitive cellular component and mitotic activity. The patients were 18-28 years old at the time of retroperitoneal lymph-node dissection. All had a previous nonseminomatous germ-cell tumor of the testis, five of which had a teratoma component. In one t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Previous experiences have highlighted cases of late WT recurrences with rabdomyosarcomatous differentiation, a fact that seems to indicate that treatment of the primary WT, designed to eradicate blastemic cells, could induce maturation of cancer cells along the epithelial and mesenchymal lines. 5 Anderson et al 6 found rhabdomyomatous differentiation after chemotherapy in 61% of surgical specimens in bilateral WT suggesting that chemotherapy may play a role in promoting myogenic differentiation of immature Wilms tumour components. Our pathological diagnosis, however, pointed to a prostatic embryonal rhabdomyosarcoma (PER), not correlated with the WT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiences have highlighted cases of late WT recurrences with rabdomyosarcomatous differentiation, a fact that seems to indicate that treatment of the primary WT, designed to eradicate blastemic cells, could induce maturation of cancer cells along the epithelial and mesenchymal lines. 5 Anderson et al 6 found rhabdomyomatous differentiation after chemotherapy in 61% of surgical specimens in bilateral WT suggesting that chemotherapy may play a role in promoting myogenic differentiation of immature Wilms tumour components. Our pathological diagnosis, however, pointed to a prostatic embryonal rhabdomyosarcoma (PER), not correlated with the WT.…”
Section: Discussionmentioning
confidence: 99%
“…12, correspond to aggregates of benign terminally differentiated rhabdomyoblasts, in the setting of teratomatous elements, and found in post-chemotherapy RPLND specimens [299]. Its recognition is important to differentiate it from rhabdomyosarcoma arising in teratoma as a somatic-type malignancy.…”
Section: Rhabdomyomatous Differentiated Tumormentioning
confidence: 98%
“…Differentiated rhabdomyomatous tumor (Fig. 7F) may occur after chemotherapy for metastatic GCT and should be distinguished from rhabdomyosarcoma [53]. It should be considered a special form of teratoma and has a prognosis similar to that of teratoma.…”
Section: Accepted Manuscriptmentioning
confidence: 98%